Modern techniques of organizing computer support for future teachers’ independent work in German language - Viktoriia O. Ustinova; Svitlana V. Shokaliuk; Iryna S. Mintii; Andrey V. Pikilnyak (CTE Workshop Proceedings, 2019)
The purpose of the study is to elucidate the theoretical and methodological aspects of computer support organization for independent work in a foreign (German) language for future teachers of different subjects. The subject of the study is a methodological technique of organizing effective computer support for future teachers to work independently in a foreign (German) language. Objectives of the study: to state the goals of studying foreign languages in its broad and narrow sense, the requirements for the results of future teachers’ training in different subjects; to explore ways of organizing computer support for future teachers’ independent work; to determine the list and purpose of the basic and auxiliary structural elements of a typical e-learning Moodle course in a foreign language; to provide methodological recommendations for the organization of future teachers’ independent work in the content of a separate training module of the Moodle course “Foreign (German) Language”. The article summarizes the experience of organizing computer support for future teachers’ independent work and the substantive and methodological features of its implementation into the process of experimental introduction of the Moodle course “Foreign (German) Language” into the educational process carried out on the basis of Kryvyi Rih State Pedagogical University.